Аналіз напівпровідникових сенсорів сучасних газоаналізаторів - Дейнеко, Наталя Вікторівна (НТУ "ХПІ", 2017)
В роботі розглядаються твердотільні газові сенсори, які є складовою сучасного газоаналізатора. За принципом функціонування газові сенсори розділені на кілька основних категорій: електрохімічні, термохімічні (термокаталітичні), масочутливі оптичні та напівпровідникові. Наведено переваги використання напівпровідникових сенсорів на основі оксидів. Проведено аналіз напівпровідникових сенсорів для сучасних газоаналізаторів, в основі якого лежить залежність чутливості сенсора від вмісту шкідливого або небезпечного газу, що міститься в повітрі, в обмеженому просторі.

The paper deals with solid-state gas sensors, which are a component of a modern gas analyzer. The effectiveness of the emergency monitoring system is largely determined by the perfection of the technical characteristics of the primary information sensors to which the gas analyzer belongs. According to the principle of operation, gas sensors are divided into several main categories: electrochemical, thermo chemical (thermo catalytic), sensitive, optical and semiconductor. Advantages of using semiconductor sensors based on oxides are given. The analysis of semiconductor sensors for modern gas analyzers is based on the dependence of the sensor sensitivity on the content of harmful or dangerous gas contained in the air in a confined space. The multifunctional properties of nanostructure semiconductors make it possible to consider them as an excellent material for manufacturing highly sensitive and selective gas sensors.
Analysis of semiconductor sensors of modern gas analyzers
Keywords: система моніторингу; оксид металу; чутливість сенсора; газові домішки; monitoring system; metal oxide; sensor sensitivity